Times Tables Write, Wipe and learn ! - Abraham, Darcie; Hemsley, Eleanor; Meredith, Samantha (Cottage Farm, UK Igloo Books Ltd, 2024)
This wipe-clean easel is the perfect introduction to multiplication. With clear activities to follow, little ones will love learning their first times tables
Science
Keywords: Science